Emotion and affect in mental imagery: do fear and anxiety manipulate mental rotation performance? - Kaltner, Sandra; Jansen, Petra (Frontiers in Psychology, 2014)
Little is known about the effects of fear as a basic emotion on mental rotation performance. We expected that the emotional arousal evoked by fearful stimuli presented prior to each mental rotation trial would enhance mental rotation performance. Regarding the influence of anxiety, high anxious participants are supposed to show slower responses and higher error rates in this specific visuo-spatial ability. Furthermore, with respect to the embodied cognition viewpoint we wanted to investigate if the influence of fear on mental rotation performance is the same for egocentric and object-based transformations. Results show that fear enhances mental rotation performance, expressed by a higher mental rotation speed. Interestingly, this influence is stimulus-specific: it is restricted to egocentric transformations. Both observation of emotional stimuli and egocentric strategies are associated with left hemisphere activation which could explain a stronger influence on this type of transformation during observation. Another possible notion is the conceptual link between visuo-spatial perspective taking and empathy based on the co-activation of parietal areas. Stronger responses in egocentric transformations could result from this specific link. Regarding the influence of anxiety, participants with high scores on the trait-anxiety scale showed poor results in both reaction time and mental rotation speed. Findings of impoverished recruitment of prefrontal attentional control in patients with high scores in trait anxiety could be the explanation for this reduced performance.